Implementation of the principle of presumption of innocence of suspects in investigations, pre-trial and trial examinations - Sukadana, Dewa Ayu Putri (Journal of Law Science, 2024)
The principle of presumption of innocence is a fundamental legal principle in the justice system to protect the rights of suspects. Law No. 8 of 1981 concerning Criminal Procedure Law (KUHAP) Article 66 of the Criminal Procedure Code explains "every person suspected of committing a criminal act is deemed innocent, until a court decision is made that has permanent legal force." This means that as long as the decision has not been changed, the defendant or suspect cannot be blamed. The application of the principle of presumption of innocence has become the main basis in the modern justice system to guarantee justice and protect individual rights. This article explores the significance and implementation of the presumption of innocence in the context of protecting the rights of suspects in the justice system. Through an overview of the literature and context analysis, this article outlines the basic principles of the principle of presumption that brings truth and its influence on the process of examining disputes. Apart from that, this article also discusses the challenges and efforts to ensure the effective implementation of the principle of presumption of illegality in legal practice.